Nombres comunes y técnicos de los peces de agua dulce de Costa Rica - Angulo, Arturo (2014)
Set out below a list of 260 common names and 60 technical names used in Costa Rica, to name a total of 154 resident species of freshwater fishes (151 native and 3 exotic). Information about the origin, meaning and use of such names at regional level, as well as updated information concerning the nomenclatural status and geographic distribution of species is provided. This information will allow better communication between technicians, scientists, political decision takers and common people with conservation purposes.